Comparative analysis of phyto-fabricated chitosan, copper oxide, and chitosan-based CuO nanoparticles: antibacterial potential against Acinetobacter baumannii isolates and anticancer activity against HepG2 cell lines - Sarfraz, Muhammad Hassan; Zubair, Muhammad; Aslam, Bilal; Ashraf, Asma; Siddique, Muhammad Hussnain; Hayat, Sumreen; Cruz, Jorrdy Neves; Muzammil, Saima; Khurshid, Mohsin; Sarfraz, Muhammad Farrukh; Hashem, Abeer; Dawoud, Turki M.; et al. (Frontiers in Microbiology, 2023)
The study aims to provide comparative analysis of chitosan (CH), copper oxide (CuO) and chitosan-based copper oxide (CH-CuO) nanoparticles for their applications in the healthcare sector. The nanoparticles were synthesized by green approach using extract of Trianthema portulacastrum. The synthesized nanoparticles were characterized using different techniques as the synthesis of the particles was confirmed by UV-visible spectrometry which showed absorbance at 300 nm, 255 nm and 275 nm for CH, CuO and CH-CuO nanoparticles, respectively. The spherical morphology of nanoparticles and the presence of active functional groups was validated by SEM, TEM and FTIR analysis. The crystalline nature of the particles was verified by XRD spectrum and the average crystallite sizes of 33.54 nm, 20.13nm and 24.14 nm were obtained, respectively. The characterized nanoparticles were evaluated for their in-vitro antimicrobial and antibiofilm potential against Acinetobacter baumannii isolates where potent activities were exhibited by the nanoparticles. The bioassay for antioxidant activity also confirmed DPPH scavenging activity for all the nanoparticles. The study also evaluated anticancer activities of the CH, CuO and CH-CuO nanoparticles against HepG2 cell lines where maximum inhibitions of 54 %, 75 % and 84 % were recorded and the activity was also confirmed by phase contrast microscopy where the treated cells exhibited deformed morphologies.